A Study on the Lotha Naga Customary Practices: North East India, Nagaland - Y J Abeni Patton, Sarika Dixit, (European Economic Letters (EEL), 2024)
To learn more about how customary government helps keep culture living and communities strong, this study looks at the Lotha Naga tribe in North East India. People from this area are called Lotha Naga, and they are a unique group. The study carefully looks at the past, governing structures, decision-making processes, and ways of adapting to new situations to explain how the complicated Lotha Naga traditional government works. A lot of the work that was done shows that traditional leaders like village heads, elders, and councils help keep cultural practices alive, settle disagreements, and bring people together. The study talks about ways to include and show everyone. It stresses how important it is for everyone to be able to agree on what should be done and for the community to be involved. The study also looks at the issues that the old way of running the government has, like how the population changes, how economic and social forces affect the system, and how outside influences can affect the country. Giving communities more power, helping them learn new skills, helping them deal with new situations, working together, and giving them official approval are some ways to keep and improve the traditional system of government.